Hubungan antara Gaya Kepemimpinan Telling dengan Kepuasan Kerja Anggota Polri pada Bidang Profesi dan Pengamanan Polda Sumatera Selatan - Febrida, Cely (Seminar Nasional Lahan Suboptimal, 2021)
Febrida C. 2021. The relationship between telling leadership style and job satisfaction of police members in the field of profession and security of the South Sumatra regional police. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang  20 Oktober 2021. pp. 451-458.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). The relationship between the leadership style of telling and job satisfaction of Police members in the field of profession and security at the South Sumatra Regional Police has not been widely studied.  The study aimed to empirically find out how big the relationship is between the leadership style of telling and job satisfaction of Police members in the field of profession and security at the South Sumatra Regional Police. The research method used empirical juridical approach with the type of field research. The leadership style of telling is a leadership style where superiors carry out one-way communication, superiors formulate and define the roles of subordinates and the decisions making is entirely the responsibility of the superiors. Job satisfaction is a positive feeling felt by Police members as a result of the compatibility between the expectations and reality of work in the form of work, promotions, salaries, superiors, and co-workers.  The results of this study showed that there was a very significant positive relationship between the leadership style of telling and job satisfaction of Police members in the profession and security sector of the South Sumatra Regional Police (r = 0.3333; F = 9.223; p = 0.003 or p < 0.01). A significance value of 0.003 showed the significance at the 1% test level (p = 0.01).  So, the higher the leadership style of telling is, the lower the job satisfaction will be, and the lower the leadership style of telling is, the higher the job satisfaction will be. It is suggested that one of the most important things for a Police organization having a highly competitive ability be the handling of human resources either from the leadership style of telling or from job satisfaction.